“Aprendizaje colaborativo en los entornos virtuales” - Perdomo Anasi, Lisbeth Johana (2022)
The social and technological changes that have occurred following the pandemic caused by COVID 19, have led to the transformation of education at all levels in which, ICTs through virtual environments, allow teachers and teachers students continue with their educational process. The objective of this research is to diagnose the use of virtual environments for the development of collaborative learning in the seventh year of Basic General Education of the José Mejía Lequerica Educational Unit of the Salcedo Canton Cotopaxi canton during the school year 2021-2022. The methodology It is part of the socio -critical paradigm, with a mixed approach, because it focuses on the description of the object of study and on the analysis of data from a given context, the types of research used are; The qualitative since the stages follow: high school, field and analytical inductive, which allowed information about the particular aspects that involve collaborative work in a virtual environment and then generalize it; The techniques that were applied is the interview and the survey with their respective instrument, the interview guide and the questionnaire. The result is the analysis of data and information on the importance of collaborative learning in virtual environments that maximize social interrelations. This project contributes to encourage the teacher to acquire digital skills regarding the diversification of virtual platforms that contribute to the development of content in the classroom in a dynamic and interactive way. It is concluded that, the development of collaborative learning in virtual environments requires technological tools that arouse interest in learning in a joint way, leaving aside the traditionalism and individualism, it also serves as methodological support as a strategy that reinforces the pedagogical competences of the teacher .